Development Authorities as Agents of Socio-Economic Change: An Historical Assessment of the Upper Nun Valley Development Authority (Undwa) in the Ndop Region of Cameroon, 1970–1995 (Nordic Journal of African Studies, 2003)
Ndop Region, the area of study, was more or less a rural backwater at the turn of the 1960s. It lacked basic social amenities, employment opportunities and vital economic structures. As a consequence, in 1970, the Cameroon Government after considerable thought established the Upper Nun Valley Development Authority, (UNVDA) to stir meaning development in the region. This was to be achieved through the development of the agricultural potentials of the region. Through agriculture, the UNVDA has influenced the lives of the people in the locale. The study isolates the social and economic changes consequent upon the establishment of the UNVDA for scrutiny. The research findings are that by 1995, the UNVDA had radically influenced the social-economic setting of Ndop. The worrying problem was, however, the appropriateness of its development paradigm.